If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 17 = 2x + 13 Reorder the terms: 17 + 6x = 2x + 13 Reorder the terms: 17 + 6x = 13 + 2x Solving 17 + 6x = 13 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 17 + 6x + -2x = 13 + 2x + -2x Combine like terms: 6x + -2x = 4x 17 + 4x = 13 + 2x + -2x Combine like terms: 2x + -2x = 0 17 + 4x = 13 + 0 17 + 4x = 13 Add '-17' to each side of the equation. 17 + -17 + 4x = 13 + -17 Combine like terms: 17 + -17 = 0 0 + 4x = 13 + -17 4x = 13 + -17 Combine like terms: 13 + -17 = -4 4x = -4 Divide each side by '4'. x = -1 Simplifying x = -1
| 2(9-7d)=-10 | | 6(-3-6n)=-198 | | 11.3d+2.5=1.3d | | 4(-7-6n)=-268 | | 2(3+4a)=-42 | | 7(-4k+6)=-182 | | 3(2+7a)=195 | | -2x-4=-9 | | 6-3(3x-2)=15 | | 2(-1)-3y=18 | | 4(5-b)=24 | | 6(-5+7d)=-30 | | 2(-2)-3y=18 | | 5(1a+6)=30 | | b-14.72=18.45 | | 4(4+3m)=16 | | 2(-5n+4)=-62 | | -20+x=x+16 | | 7(9+3m)=168 | | 4(-6t-1)=-148 | | 2(7-2t)=42 | | 3(9-2d)=3 | | df=g-10 | | 6(-2t+8)=-84 | | 7(-5+n)=-28 | | 4(2+a)=44 | | 6(2a+10)=96 | | 5(5+6n)=-215 | | 15a-54=-3 | | 7(-5+3k)=175 | | an=3+(n-1)(-5) | | (2x+10)=(86+x) |